Performance of two genetic lines of Oreochromis spp. in a conventional recirculating system. - Zúñiga-Vargas, Esteban (2026)
The study evaluated the performance of Oreochromis aureus and Oreochromis niloticus × aureus (Rocky Mountain White), during 90 days of development in a closed recirculating system located in La Unión, Cartago, Costa Rica. Individuals of Oreochromis aureus (30 ± 1 g) and Oreochromis sp. var. Rocky Mountain White (45 ± 1 g) were used. Sixty tilapias per species were selected, forming six experimental units of 10 individuals in a completely randomized unifactorial experimental design with species as treatments.  The system featured a three-layer sump tank and a mechanically biofiltered moving bed. Mortality and water quality were monitored (temperature, salinity, and dissolved oxygen instrumentally; alkalinity, pH, nitrites, nitrates, and total ammonia nitrogen through colorimetry), with temperature partially adjusted using thermostats. Population parameters and biosystem stability limits were estimated through statistical process control. Growth variables, feed conversion, thermal growth coefficient, viscerosomatic index, head-body ratio, and carcass yield were evaluated over time in the fish. Additionally, linear and exponential weight prediction models based on width and length were estimated. Oreochromis aureus exhibited greater growth and efficiency than the hybrid, with lower initial mortality due to nitrites. Yield was higher in males of both genetic lines. It is concluded that Oreochromis aureus grows more efficiently than the hybrid, according to the studied growth and efficiency variables.